2019
DOI: 10.1016/j.ijrobp.2018.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Outcomes of a Feasibility Study of Inverse-Planned, Multibeam Intensity Modulated Radiation Therapy in Node-Positive Breast Cancer Patients Receiving Regional Nodal Irradiation

Abstract: Background: Multi-beam IMRT enhances the therapeutic index by increasing the dosimetric coverage of the targeted tumor tissues while minimizing volumes of adjacent organs receiving high doses of RT. The tradeoff is that a greater volume of lung is exposed to low doses of RT, raising concern about the risk of radiation pneumonitis (RP).Methods: Between 7/2010-1/2013, patients with node-positive breast cancer received inverseplanned, multibeam IMRT to the breast/chest wall and regional nodes including the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Further longer-term studies in more patients are needed to confirm these results and establish the role of TD in these patients. Some studies demonstrated a longer favorable clinical outcome of postoperative radiation therapy including the regional lymph node area in patients with breast cancer using fix beam IMRT rather than TD using TomoTherapy [34]. These data support the application of TD to this disease.…”
Section: Discussionmentioning
confidence: 63%
“…Further longer-term studies in more patients are needed to confirm these results and establish the role of TD in these patients. Some studies demonstrated a longer favorable clinical outcome of postoperative radiation therapy including the regional lymph node area in patients with breast cancer using fix beam IMRT rather than TD using TomoTherapy [34]. These data support the application of TD to this disease.…”
Section: Discussionmentioning
confidence: 63%
“…Firstly, the value of isolated dose-volume metrics as predictors of pulmonary toxicity is contentious given the relative lack of data specific to breast irradiation, the relatively low rate of RP, and the absence of a clear threshold dose for RP [19]. Ho et al [38] recently found that the lung V20Gy and V5Gy were not predictive for grade three RP for breast cancer patients receiving addition RNI. In contrast, Lind et al [39] demonstrated through multivariate modelling that the ipsilateral lung V20Gy predicted for radiologic and symptomatic pneumonitis, as well as pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT has been proposed as a heart sparing technique, although ndings regarding MHD have been con icting. In a recent prospective study from the Memorial Sloan-Kettering Cancer Center [17], an MHD of 13.2 Gy (range, 8.6-20 Gy) was reported in patients with left-sided breast cancer who received multibeam IMRT. In a Korean dummy-run study (KROG 1901), 21 institutions received a representative case and were requested to create a complete RT plan from target delineation according to respective institutional protocols [18].…”
Section: Discussionmentioning
confidence: 99%